Factors affecting the circulation of agricultural land in Ukraine - Synieutskyi, A. (Land Management, Cadastre and Land Monitoring, 2026)
The article substantiates the expediency of analysing the agricultural land market in Ukraine as a system in which market results (prices, transaction volumes, liquidity, transaction costs) are shaped by the simultaneous action of institutional and legal changes, economic conditions, the quality of land as natural capital, and spatial security risks in wartime. The aim is to classify the factors that determine demand, supply, price expectations and transaction costs, and to explain the mechanisms of their manifestation within the economy of natural resource use and good land governance. The methodology combines a systematic approach, comparative analysis, content analysis of scientific and analytical sources, as well as legal analysis of regulations on land circulation, cadastre, valuation and protection. The empirical context is supported by generalised quantitative indicators of market functioning in 2021–2025 (dynamics of weighted average prices, transaction intensity, ratio of market price to normative monetary valuation), as well as security risk parameters (scale of potential explosive contamination of territories). As a result, nine groups of factors (natural resources, economic, social, demographic, technological, cultural, legal, political and security) were identified and a logic for their operationalisation through channels of influence and a set of measurable indicators for land monitoring was proposed. The scientific novelty lies in the methodologically correct inclusion of soil condition parameters and war-related access restrictions/limitations as risk and cost components in factor analysis of the market with a focus on evidence-based management. The practical significance lies in the possibility of applying the proposed scheme to reduce information asymmetry, increase transaction transparency, and prioritise land protection and restoration measures at the national and local levels.Received: 28.02.2026;Accepted: 12.03.2026;
Keywords: agricultural land market; influencing factors; natural capital; soil degradation; transaction costs; land cadastre; normative monetary valuation; military risks; land monitoring; circulation of agricultural land